Pemikiran Pendidikan Imam Al-Ghazali dan Relevansinya dalam Sistem Pendidikan Islam Kontemporer - Madhar, Madhar (STAI Asy-Syukriyyah, 2024)
This study examines the relevance of Imam Al-Ghazali's educational thought in contemporary Islamic education, focusing on goals, curriculum, teaching methods, and the teacher's role. Using a literature review with descriptive-analytical methods, the study analyzes Al-Ghazali’s ideas and related literature. The findings highlight that Al-Ghazali’s holistic educational concept, which integrates religious and worldly knowledge, provides solutions to modern challenges, such as moral crises, materialism, and globalization. Imam Al-Ghazaliviewed education as a means of shaping noble character and closeness to Allah SWT, with a balanced approach to cognitive, emotional, and spiritual development. His ideal curriculum combines religious and worldly sciences, while teaching methods emphasize exemplary behavior, reflection, and personalized approaches. Teachers are regarded as moral exemplars with a significant responsibility for guiding students intellectually and ethically. This study emphasizes the importance of integrating spiritual values into modern Islamic education curricula and enhancing teachers' roles as character builders. These findings contribute significantly to the development of an Islamic educational system that prepares intellectually capable, morally upright, and ethical generations to effectively address global challenges.